HIGH-RESOLUTION (2-7 KHZ) ACOUSTIC AND GEOMETRIC CHARACTERS OF SUBMARINE CREEP DEPOSITS IN THE SOUTH KOREA PLATEAU, EAST SEA - Lee S.H.; Chough S.K. (My University, 2001)
A synthesis of high-resolution (Chirp, 2-7 kHz) seismic profiles in the South Korea Plateau reveals that large masses of wavy stratified sediment (≈60-90 m thick) cover broad, gently sloping (<0·5°) ridges in water depths of 1000-2000 m. The wavy stratified sediment (WSS) is characterized by wavy (0·2-5 km in wavelength and <15 m in relief), continuous reflective layers with a basal deformed zone that overlies undeformed, strong reflectors. The WSS exhibits systematic variation in wave dimensions and thickness of internal reflective layers with changes in slope gradient. The troughs of the waves are commonly associated with internal growth faults, and wave amplitude generally increases with subbottom depth. On steep slopes around the ridges, the WSS masses are bounded downslope by slide and slump deposits including slightly translated or rotated WSS blocks. The acoustic and geometric characters, and association with downslope slides and slumps on the steeper slopes, suggest that the WSS masses were most probably formed by slow creep movement before slope failure. In the absence of significant sediment input to the South Korea Plateau, the deep (1000-2000 m in water depth) mass movements were probably triggered by earthquakes that have occurred frequently in this region. Some slightly displaced, intact WSS blocks in the associated slides and slumps downslope reflect a progressive evolution from submarine creep into slide and slump.
Keywords: EAST SEA; HIGH-RESOLUTION (CHIRP, 2-7 KHZ) SEISMIC PROFILE; SOUTH KOREA PLATEAU; SUBMARINE CREEP; SUBMARINE MASS MOVEMENTS